FIRM PERFORMANCE: A COMPARATIVE ANALYSIS OF OWNERSHIP STRUCTURE - Taqadus Bashir; Anum Riaz; Sabeen Butt; Abida Parveen (European Scientific Journal, ESJ, 2013)
Majority of firms in the world have controlling shareholders, usually a family or a state and in few other cases, single individual controls manyfirms under an umbrella. The study aimsto investigate the relationship between ownership structure and performance of firms. A sample of 100 firms listed on Karachi stock Exchange (including 50 private and 50 public firms) for time period 2007 to 2011 were used for analysis. Firm’s performance is measured by accounting based measures as well as market based measures. Return on asset, Profitability,Leverage,Asset turnover, Earning per share and Tobin’s Q are taken as independent variableand Equity is used as a dependent variable. The statistical tools Mean, OLS, Correlation and T-Test were used for analysis of data. It was concluded that privately owned firms performs better than publicly owned firms. All independent variables except Tobin’s Q indicated a significant relationship with dependent variable which ultimately contributes toward a higher performance. Statistical differences are insignificant between private and public owned firms.